Analisis Tingkat Pendapatan Pengrajin Songket di Desa Sukarara - khansa khaerunnisa khansa (Program Studi Ekonomi Pembangunan, 2025)
Sukarara Village is known as a center for songket crafts in Central Lombok, with around 70% of its population working as songket craftsmen. The existence of weaving crafts in Sukarara Village has a high socio-economic impact, one of which is increasing income. There are many important factors that influence income, namely the level of length of work, the amount of production, and the price of production. The research location is the Songket Woven Fabric craft center in Sukarara Village in Jonggat District, Central Lombok Regency. This research uses a quantitative approach. The sample used was 44 songket craftsmen in Sukarara Village whose population was songket weavers. The results of this research are that production prices have the most significant influence at 87%, production quantities also have a significant influence on income at 48.2%. Length of work does not have a significant influence at 2.9%. Further research can be carried out to explore other factors that might influence the income of Songket craftsmen in Sukarara Village, Central Lombok. This is important to obtain a more comprehensive picture of the dynamics of the songket craft industry and the efforts that can be made to develop this industry in a sustainable manner.